2018
DOI: 10.1111/ijn.12687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a nurse‐led intervention programme on professional quality of life and post‐traumatic growth in oncology nurses

Abstract: This nurse-led intervention programme was effective in improving the professional quality of life and post-traumatic growth of oncology nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
0
46
1
7
Order By: Relevance
“…Finally, Yilmaz et al [35] found that a nurses-led intervention program with two sessions about compassion fatigue, coping methods, oncology patients, breathing exercises, baksi dance, mandala painting, relaxation, and questions about death and empathy and two counselling follow-ups with motivational messages via a smartphone was effective in reducing compassion fatigue and burnout and increasing compassion satisfaction.…”
Section: Interventions For Reducing Compassion Fatiguementioning
confidence: 99%
“…Finally, Yilmaz et al [35] found that a nurses-led intervention program with two sessions about compassion fatigue, coping methods, oncology patients, breathing exercises, baksi dance, mandala painting, relaxation, and questions about death and empathy and two counselling follow-ups with motivational messages via a smartphone was effective in reducing compassion fatigue and burnout and increasing compassion satisfaction.…”
Section: Interventions For Reducing Compassion Fatiguementioning
confidence: 99%
“…Özet az çalışma vardır. [12,13] Hemşirelerle yapılan çalışmalarda tükenmişliğin prediktörü olduğu belirtilen duygusal tükenmişlik düzeyinin yüksek olduğu belirlenmiştir. [14] Ayrıca araştırmalar incelendiğinde daha çok tükenmişliğin ele alındığı profesyonel yaşam kalitesinin diğer boyutları olan merhamet yorgunluğu ve merhamet memnuniyetinin birlikte incelenmediği görülmektedir.…”
Section: Gülay Yılmaz 1 Besti üStün 2 1 Bozok üNiversitesi Sağlık Biunclassified
“…Merhamet yorgunluğunun fark edilip müdahale edilmemesi sonucunda stres ile bağlantılı birçok kronik hastalığa neden olabileceği de belirtilmiştir. [31] Merhamet yorgunluğunun hospis hemşireleri, [34] afet mağdurları ile çalışan toplum sağlığı hemşireleri, [35,36] onkoloji hemşireleri, [12,37,38] acil hemşireleri, [39] yoğun bakım hemşireleri [40,41] gibi kritik hastaların olduğu birimlerde çalışanlarda daha yaygın olduğu görülmüştür. Bu birimlerde çalışan hemşirelerin yaşadığı merhamet memnuniyeti ve merhamet yorgunluğunu yani genel olarak profesyonel yaşam kalitesini sosyodemografik ve çalışma ortamına ait bazı faktörler etkilemektedir.…”
Section: Profesyonel Yaşam Kalitesini Etkileyen Faktörlerunclassified
See 2 more Smart Citations